Autoempreendedorismo, empoderamento e precariedade: mulheres feirantes e as possibilidades de geração e manutenção de renda frente à crise da pandemia da covid-19 - Ribas, Gabriela Bastos (2023)
Changes in the Brazilian labor market arising from the productive restructuring process significantly marked the beginning of flexible accumulation, generating implications for the “class that lives from work”, and even more so for the lives of Brazilian working women. With the Covid-19 pandemic, the labor scenario also suffers different implications, such as, mainly, the increase in unemployment. In the city of Santa Maria, in Rio Grande do Sul, in the first months of the pandemic there were around 10,000 layoffs, 4,000 of which in just 30 days. One of the alternatives found by workers was self-employed, self-managed, and informal work, which currently corresponds to about 39.6% of the employed Brazilian population, a category in which 70% are women, and it is in this scenario that entrepreneurship spreads as an alternative. In this sense, the following research aims to understand how the search for informal work took place, what are its implications, and the relationship between entrepreneurship and empowerment, based on reports from female marketers at Feito por Mulheres, a collective organization in the form of a street market, which emerged in the context of a pandemic in the city of Santa Maria, with a proposal to generate income only for women. This research also addresses the dynamics of micro-resistance in the face of the work crisis and the perception of marketers about the informal and formal modality in Brazil, in addition to problematizing the limits of self-employment, the influence of family history, and the construction of identity entrepreneurs. For the construction of this research, a Marxist theoretical framework was used, as well as readings of the sociology of work, and, in large part, the contributions of materialist and classist feminism. The chosen methodology is qualitative, using semi-structured interviews, socioeconomic questionnaires, and participant observation in some editions of the street market.